Outsourcing and its Enabled Service Sector in the Globalised Scenario: Emerging Challenges - Jagadees Pandi, S. (Indian Journal of Marketing, 2006)
India is a country that can feel the pulse of the society and change its image accordingly in spite of its huge diversity. Now the Business Process Outsourcing sector (BPO) is making waves in the Indian industrial landscape. It is one of the most dynamic sectors after the IT boom that swept across the country over a decade. Passing through the Information Technology (IT) phase, the country has gradually turned itself into a hub center of IT and IT enabled services (ITES).